Skyddade träd i kyrklig kulturmiljö : förvaltning av trädens kulturhistoriska värden, biologiska värden och säkerhet - Ringdahl, Camilla (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2019)
Trees, and usually old trees, occur in many cemeteries and are important as they contribute with different values. This work focuses on two of these values, cultural-historical values and biological values as well as safety that is a significant factor in tree management. The fact that trees in cemeteries and their values can be legally protected is also dealt with in this work and how it affects the management or planning of trees in a cultural environment. The purpose of the work has therefore been to find out through a case study whether it is possible to reconcile cultural-historical and biological interests with safety requirements when establishing a tree plan for a cemetery.